Boredom at work: The contribution of Ernst Jünger. (September 2022) - Watt, Peter; Weibull, Fredrik
This paper interrogates the phenomenon of boredom at work by considering Ernst Jünger's potential contribution. We contend that Jünger offers an important yet overlooked alternative to the dominant perspectives of boredom in Management and Organization Studies (MOS), which are largely composed of 'simple' psychological diagnoses and managerial prescriptions. Such studies largely understand boredom as a localised experience at work which can be overcome by targeted managerial prescriptions, techniques and interventions. In contrast we show how Jünger understands boredom from a 'profound' perspective as a central feature of modernity. This is premised on Jünger's broader critique of the bourgeois values that define 20th and 21st century managerial work and organization. Jünger's cultural-historical perspective is therefore aligned to the discrete field of Boredom Studies. By addressing how Jünger understands 'work' as the defining feature of the modern age, his critique situates the phenomenon of boredom at work within the broader social, institutional and cultural order of the 21st Century. While Jünger does not set out to provide a theory of boredom as such, we reconstruct such a theory through an exegesis of his writing on 'work' and 'danger'. This reveals boredom and danger as phenomenologically intertwined concepts, which is an understanding of boredom that has not been considered in MOS or Boredom Studies. It is through this, we argue, that Jünger's conception of work holds the potential for a powerful critique and understanding of boredom at work under the contemporary regime of neoliberal managerialism.